2013
DOI: 10.4081/jear.2013.e8
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic compartmentalization and activity in the midgut of Andrallus spinidens Fabricius (Hemiptera: Pentatomidae)

Abstract: Digestive proteolytic activity in the alimentary canal of Andrallus spinidens, a potential biocontrol agent of lepidopteran larvae, was studied by considering enzyme compartmentalization and diversity. The alimentary canal of adults consists of a foregut, a four- sectioned midgut, namely V1 to V4 (ventriculus), and a hindgut. The optimal pH for general proteolytic activity was found to be at pH 8 with a small peak at pH 6. Results revealed that there are several specific protease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 22 publications
3
10
0
Order By: Relevance
“…N. viridula has a midgut that can be divided into four morphologically distinct sections along its anterior-posterior axis termed M1 (extreme anterior) to the extreme posterior (M4), which is separated from the first three anterior portions by a selective valve [6]. Some physiological roles have been assigned to these compartments; M3 has been implicated in nutrient digestion and the M4 region has long been known to harbor symbiotic bacteria which appear to be essential for growth [7][8][9]. However, neither the physiological roles or expression profiles of these gut compartments are fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…N. viridula has a midgut that can be divided into four morphologically distinct sections along its anterior-posterior axis termed M1 (extreme anterior) to the extreme posterior (M4), which is separated from the first three anterior portions by a selective valve [6]. Some physiological roles have been assigned to these compartments; M3 has been implicated in nutrient digestion and the M4 region has long been known to harbor symbiotic bacteria which appear to be essential for growth [7][8][9]. However, neither the physiological roles or expression profiles of these gut compartments are fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, some properties of insect chymotrypsins contrast to those of vertebrate chymotrypsins, such as their instability at acid pH and their strong inhibition by soya bean trypsin inhibitor. Sorkhabi-Abdolmaleki et al (2013) demonstrated pH 9 and pH 9-10 for trypsin-like, chymotrypsin-like proteases of Andrallus spinidens, respectively. Sharma et al (1994) found a pH of 11 and 8 as the optimal values for activities of trypsin and chymotrypsin respectively in Tipula abdominalis larvae.…”
Section: Discussionmentioning
confidence: 93%
“…The high molecular mass trypsins found in some lepidopteran (Brito et al., ; Oliveira et al., ; Zibaee et al., ) and coleopteran species (Wagner et al., ; Hosseininaveh et al., ; Silva et al., ; Castro‐Guillén et al., ) have been suggested to result from oligomerisation, which interferes with binding of proteinaceous inhibitors present in their food. Also, the maintenance of high trypsin and proteinase activity within wide pH range in insects that use different isozymes and different mechanistic classes of proteinases, enables efficient digestion of proteins under variable gut conditions or simply reflects divergence in structure important for digestion of heterogeneous food proteins and circumventing proteinase inhibitors (Ortego et al., ; Zeng et al., ; Silva et al., ; Wright et al., ; Castro‐Guillén et al., ; Sorkhabi‐Abdolmaleki et al., ; Delkash‐Roudsari et al., ).…”
Section: Structural Diversity Of Insect Digestive Trypsinsmentioning
confidence: 99%
“…Although large differences in the major mechanistic classes of proteinases and proteinase structures have been recorded in phylogenetically distant species with similar feeding habits (Hughes & Vogler, ; Terra & Ferreira, ), it is reasonable to assume that the chemical composition of food as well as diet heterogeneity had a large impact on evolutionary diversification of proteinases. Specific food type may favor a shift to new proteinases (Murdock et al., ; Christeller et al., ; Johnson & Rabosky, ; Lopes et al., ) or the use of multiple mechanistic classes (Overney et al., ; Ortego et al., ; Silva et al., ; Hernández et al., ; Zhang & Brune, ; Sorkhabi‐Abdolmaleki et al., ) and multiple proteinase isozymes (Mazumdar‐Leighton & Broadway, ; Marshall et al., ; Spit et al., ) to digest proteins. Besides the evolutionary novelties in proteinase classes and structures, food composition may have both short‐ and long‐term influence on the regulation of proteinase activity.…”
Section: Introductionmentioning
confidence: 99%